An electromechanical behavior of reduced graphene oxide fiber. (August 2016) - Meng, Fancheng; Wang, Miao; Lu, Weibang; Li, Qingwen; Chou, Tsu-Wei; Zheng, Lianxi
Abstract: An electromechanical response of the chemically reduced graphene oxide (rGO) fiber is reported. The rGO fiber has a tensile strength of 159 MPa, and an electrical conductivity of 170 S/cm. When a current is applied, an immediate load-drop, up to 82% of the original loading, can be observed. Such a load-drop is partially reversible when the current is withdrawn. Higher current density (5–20 mA) and higher relative humidity (40%–80%) result in larger load changes. Joule heating induced dynamic absorption and desorption of water molecules, which further induce the rGO sheet sliding and elastic deformation are responsible for this actuation.